1995
DOI: 10.1111/j.1749-6632.1995.tb44618.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression and Phosphorylation of Mouse Osteopontina

Abstract: Osteopontin is expressed in many different cell types and has been proposed to play several functions. Distinct forms of the protein have been detected. Various tissues and cell lines from mouse, however, exhibit two classes of transcripts with different 5'-untranslated ends but with an identical coding region (exons II through VII). These transcripts do not arise from the alternative splicing of coding exons. These results suggest that posttranslational modifications of osteopontin, such as phosphorylation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Examining OPN secretion into the culture medium, significant amounts were detected in the culture medium of the pIRES‐hrGFP‐1a‐OPN‐transfected vSMCs, but not in vector controls (Figure 1, lower panel). Multiple OPN bands were specifically recognized by the OPN antibody, confirming previous observations (Saavedra et al, 1995; Parrish and Ramos, 1997) that OPN is extensively modified before secretion into the culture medium (Figure 1, lower panel). Ponceau S staining before antibody probing was used as a loading control.…”
Section: Resultssupporting
confidence: 90%
“…Examining OPN secretion into the culture medium, significant amounts were detected in the culture medium of the pIRES‐hrGFP‐1a‐OPN‐transfected vSMCs, but not in vector controls (Figure 1, lower panel). Multiple OPN bands were specifically recognized by the OPN antibody, confirming previous observations (Saavedra et al, 1995; Parrish and Ramos, 1997) that OPN is extensively modified before secretion into the culture medium (Figure 1, lower panel). Ponceau S staining before antibody probing was used as a loading control.…”
Section: Resultssupporting
confidence: 90%
“…In keeping with this interpretation is our ®nding that the major intracellular form of OPN present in cell lysates (of both 21T series cells and MDA-MB-435 cells) is the low molecular weight, 66 kDa form. The relative biological activity of the di erent MW forms of OPN is at present largely unknown, although it has been suggested that transglutaminase crosslinking of extracellular matrix components may be important in stabilizing cellular adhesive contacts (Menter et al, 1991), that sialylation and phosphorylation may modify OPN functions/activity (Shanmugam et al, 1997;Saavedra et al, 1995), and that the thrombin cleavage fragment containing the GRGDS sequence is more e ective at promoting haptotaxis (Senger and Perruzzi, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…These modifications can also affect the biological properties of OPN, as discussed later. (2000) (a) Phosphorylation Phosphorylation of OPN, catalyzed by several kinases, can take place on tyrosine, or on serine and threonine residues (Saavedra et al, 1995;Lasa et al, 1997). Potential serine and threonine phosphorylating enzymes include casein kinases I and 11, Golgi kinases, cAMP-and GMP-dependent kinases, protein kinase C, and ectokinases.…”
Section: (V) Post-translational Modificationsmentioning
confidence: 99%